A zip code study of socioeconomic, demographic, and household gendered influence on the residential energy sector. (November 2016) - Elnakat, Afamia; Gomez, Juan D.; Booth, Nathlie
Abstract: This study investigates the influence of socioeconomic and demographic characteristics of the population on residential energy utilization patterns at the ZIP code level in San Antonio, Bexar County, Texas. The City of San Antonio, Texas is the seventh most populous city in the United States and second in the State. Variables analyzed include gender, median age, median income, educational attainment, occupancy, population density, total energy, per capita energy and per home energy. Statistically significant relationships between variables are discovered and highlighted in support of public policy development to ensure long-term, and cost-effective energy management. Highlights: Influence of socio-demographics on household energy utilization is evident. Gender influence is significant in understanding residential energy consumption. Energy consumption increases significantly around the median age of 40–55. Owner occupied single-family dwellings use more total energy than renter units. Predictive analyses of social variables for good energy policy are prescribed.